The Effectiveness of Quizizz Application in Enhancing Students' Vocabulary Mastery based on Their Learning Styles - Marzon Efendi; Iis Sujarwati; Alamsyah Harahap (JEELS (Journal of English Education and Linguistics Studies), 2025)
One such technological tool that can enhance students' engagement and learning outcomes is Quizizz, a game-based learning platform. Meanwhile, students’ learning styles—whether visual, auditory, or kinesthetic—play a crucial role in how effectively they absorb new information. However, there is still limited research exploring the combined effect of learning styles and digital platforms on vocabulary mastery, especially at the elementary school level. This study aims to examine significant differences in students’ English vocabulary mastery between experimental and control classes. Additionally, it seeks to determine differences in vocabulary mastery among students with auditory, kinesthetic, and visual learning styles and to investigate the interaction between the use of the Quizizz application and learning styles. A quasi-experimental design with a 2x3 factorial arrangement was employed. The participants consisted of 50 fifth-grade students divided into an experimental class (which used Quizizz) and a control class (which did not). Based on the results of the independent samples t-test and two-way ANOVA, the students in the experimental class achieved significantly higher post-test scores than those in the control class. However, there were no significant differences in vocabulary mastery among students with different learning styles. Furthermore, the two-way ANOVA indicated no significant interaction between the use of Quizizz and students’ learning styles. These findings suggest that while Quizizz is an effective tool for improving vocabulary mastery, its effectiveness is consistent across different learning styles.